Rescate de la identidad cultural del cantón Mocache a través de los juegos populares-2015 - Sangoquiza Ibarra, Raquel Amelia (2015)
The popular games are activities that keep specific characteristics and identified a particular sector or community, which they were transmitted from one generation to another and practiced mostly by children. This research work tries to rescue cultural identity of the canton Mocache through the popular games. It was concluded that the mentioned games, such as hopscotch, the wolf, the bridge is broken, the kite, the bolicha, greasy pole, burnt bread and the judge told the priest, the cultural heritage of the canton Mocache recorded and he devised a rescue plan proposed this heritage through activities to be implemented in educational institutions with the support of the Autonomous Government Decentralized Mocache Canton, and a guide to the popular games are designed. The games were practiced in times of recess and recreation for children, however, it has been losing its information over time so the record is limited to relate their existence and influence in the daily life of children. The guide is designed to be used as a means of consultation to facilitate investigations and subsequent socialization to recover the popular games as a fun activity to strengthen the abilities, skills, leadership and decision making in children, which be part of the new company, according to the needs and requirements of the social environment in which they operate.